DEVELOPMENT OF THE LEARNING PROCESS MANAGEMENT IN THE CONTEXT OF DIGITIZATION - Voskovskaya, Anzhela; Karpova, Tatiana; Rostovtseva, Polina; Guseva, Natalia; Shelygov, Aleksandr (Revista Inclusiones, 2020)
The article is devoted to the development of approaches to improving the management of the learning process in the context of digitization. The massive and ramified formal education system does not meet the needs of the labor market and is unable to form high-quality labor resources. It does not work for the autonomous well-being of citizens and significantly reduces their employment opportunities and capitalization, that is, the economy and the country, in general, are losing. Approaches, solutions, and initiatives for the development of digital literacy through academic formal education and non-formal education will differ based on their specifics. The key solution to the problem is a combined strategy, in which there are long-term measures and scales inherent in the state education system and short-term rapid measures that are more relevant for implementation in the digital education segment.